8 MONUMENT TRISULA SEBAGAI BUKTI PENUMPASAN SISA-SISA G 30 S PKI DI BLITAR SELATAN - yatmin, yatmin (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT The background of this study and the fact the field observations, that the young generation today lacks a sense of nationalism and patriotism to the country, and even the little they know about the history of Indonesia, especially the history of the monument Trisula. It is apparent from the number of visitors who come to the Trident and even rare monuments of people who know about Trident Monument in South Blitar. History Monument Trident is originally with the arrival of PKI from outside the area to the south of Blitar, where they teach communism to the people, that the Communist Party was the party of the workers and farmer. Because the G30S / PKI, namely the murder of the Armed Forces General in alligator holes made by the PKI, thus making the government requires PKI eradicate completely. TNI know that many PKI members who fled to the south of Blitar, then the military, police and people together crush the PKI in Blitar south-named Trident operation. Many casualties in the operation, in order to honor the hero in maintaining the purity of Pancasila and wholeness NKRI then place it was established Monuments Trident, as proof that the place that's the end of the trip the communist parties in Indonesia. Key words: Trisula monument, PKI, south Blitar.